2021
DOI: 10.1002/bmc.5106
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum–effect relationship between GC‐QTOF‐MS fingerprint and antioxidant, anti‐inflammatory activities of Schizonepeta tenuifolia essential oil

Abstract: Schizonepeta tenuifolia (Benth.) Briq, a traditional Chinese medicine, is an annual herbaceous plant that is widely distributed in China, Japan, and Korea. The essential oil (EO) of S. tenuifolia has antioxidant and anti-inflammatory properties. However, the components contributing to its antioxidant and anti-inflammatory activities remain unclear. This study was aimed at investigating the spectrum-effect relationship between GC-MS fingerprint and the antioxidant and anti-inflammatory effects of S. tenuifolia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Mathematical models are often used to evaluate the relationship between the fingerprints of TCM compounds and their efficacy as well as to determine the chromatographic peaks closely related to pharmacodynamics from the fingerprints ( Feng et al, 2020 ; Bai et al, 2021 ). We had previously investigated the in vitro spectrum-activity relationship of YYTNG ( Yu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mathematical models are often used to evaluate the relationship between the fingerprints of TCM compounds and their efficacy as well as to determine the chromatographic peaks closely related to pharmacodynamics from the fingerprints ( Feng et al, 2020 ; Bai et al, 2021 ). We had previously investigated the in vitro spectrum-activity relationship of YYTNG ( Yu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…e grey correlation degree of all peaks was higher 10 Journal of Chemistry than 0.6, which indicated that the antioxidant activity was caused by common functions of several components [32].…”
Section: Gra Of Antioxidant Spectrum-effect Relationshipmentioning
confidence: 94%
“…For example, chlorogenic acid and 3,4-dicaffeoylquinic acid from Lonicerae Japonicae Flos and Lonicerae Flos were selected as the major antibacterial components by spectrum-effect relationships [31]. Menthone, isomenthone, pulegone, piperitone, and β-caryophyllene were identified as the dominant constituents responsible for the antioxidant and anti-inflammatory activities of S. tenuifolia essential oil [32]. In Chinese Pharmacopoeia (2020 edition), the contents of picrocrocin were newly used as the quality control standard for saffron, coupled with the content of crocins I and II.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical studies showed that SS contained volatile organic compounds (VOCs), flavonoids, and organic acids, among which VOCs were the main medicinal component, and pharmacological activities of VOCs possess anti-inflammatory, antineoplastic, and antiviral properties [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. Studies on SS mainly focus on volatile oil extraction and bioactive ingredients, but the overall characterization of VOCs of SS from different sources is not comprehensive enough [ 8 ].…”
Section: Introductionmentioning
confidence: 99%